2009
DOI: 10.1007/s10526-009-9256-3
|View full text |Cite
|
Sign up to set email alerts
|

Reproductive performance of Nesolynx thymus (Hymenoptera: Eulophidae) as influenced by host (Musca domestica) size

Abstract: An investigation was conducted to understand the influence of host size on the reproductive performance of Nesolynx thymus, an ecto-pupal parasitoid of the uzi fly, Exorista bombycis, inflicting 10-20% loss to silkworm crops in the southern silk producing states of India. Two day-old adults of N. thymus were allowed to parasitize pupae of M. domestica, categorized into big and small at a parasitoid-host ratio of 1:20. After parasitoid adult eclosion, data on parasitization rate, developmental duration, male, f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
1
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 42 publications
2
1
0
Order By: Relevance
“…Increased parasitism resulting with the increased exposure time of parasitoid to host pupae observed in our study was also reported in Oomyzuz sokolowskii (Kurdjimov) where the parasitism rate doubled from 40% after 24 h exposure to 80% after 72 h of exposure to third-instar Plutella xylostella (L.) (Torres et al, 2010). Variation in parasitism level ranging from 20-80% in T. howardi on Chilo partellus (Swinhoe) was mainly due to exposure period (Baitha et al, 2004). In our study, 48 h exposure period showed higher level of parasitism and the with higher female progeny.…”
Section: Fig 2 Proportion Of Female and Male N Thymus Emerging From Varying Host Size Pupaesupporting
confidence: 84%
See 1 more Smart Citation
“…Increased parasitism resulting with the increased exposure time of parasitoid to host pupae observed in our study was also reported in Oomyzuz sokolowskii (Kurdjimov) where the parasitism rate doubled from 40% after 24 h exposure to 80% after 72 h of exposure to third-instar Plutella xylostella (L.) (Torres et al, 2010). Variation in parasitism level ranging from 20-80% in T. howardi on Chilo partellus (Swinhoe) was mainly due to exposure period (Baitha et al, 2004). In our study, 48 h exposure period showed higher level of parasitism and the with higher female progeny.…”
Section: Fig 2 Proportion Of Female and Male N Thymus Emerging From Varying Host Size Pupaesupporting
confidence: 84%
“…The reduction in parasitisation in exposure period beyond 48 h may be due to occurrence of superparasitism. A condition that was reported when T. howardi against Chilo partellus (Baitha et al, 2004). This study clearly indicates that 24-48 h is a suitable exposure period to adopted during mass production of parasitoids.…”
Section: Fig 2 Proportion Of Female and Male N Thymus Emerging From Varying Host Size Pupaesupporting
confidence: 57%
“…The shortest duration from egg to adult T. diatraeae in O. invirae pupae than in those of B. sophorae can be attributed to the shorter pupa stage of the host, because the faster metabolism of the host can reduce the parasitoids (Smethurst et al, 2004). Moreover, competition among immature T. diatraeae in the smaller O. invirae pupae and consequently the lower food resources available compared to larger B. sophorae pupae may also resulted in the development duration in that host (Aruna and Manjunath, 2010). The longest duration of T. diatraeae development in B. sophorae pupae can reduce the chances of host survival by it increases the period vulnerable to predators, pathogens or the host response (Benrey and Denno, 1997).…”
Section: Discussionmentioning
confidence: 99%